Potatoes Incorporated into a Higher Protein Diet for 16-Weeks Do Not Influence Cardiometabolic Health in Adults with Metabolic Syndrome: A Pilot Study. (29th May 2020) - Walker, Sam; Baum, Jamie; Hawley, Aubree; Tacinelli, Angela; Enderlin, Drake; Fellinger, Mckenzie
Abstract: Objectives: To determine if consuming four servings of white potatoes, processed potato products, or starchy carbohydrates for 16 weeks, as part of a higher protein diet, influence markers of cardiometabolic health in adults with metabolic syndrome. Methods: Eleven adults with metabolic syndrome were randomly assigned to one of three higher protein diets incorporating different carbohydrate sources: 1) 4 servings of potatoes/week (P; n = 4; 4 female; 48.3 ± 9.4 y; 92.4 ± 9.6 kg; 36.3 ± 4.3 BMI); 2) processed potatoes (PP; n = 2; 1 female, 1 male; 53.0 ± 15.0 y; 81.4 ± 17.0 kg; 29.6 ± 3.0 BMI); or 3) starchy carbohydrate (SC; n = 5; 4 female, 1 male; 33.6 ± 5.0 y; 95.1 ± 18.2 kg; 35.3 ± 4.7 BMI). Data was collected at baseline, 4, 8, 12, and 16 weeks. Glucose, cholesterol, and triglycerides were analyzed using a Cholestech LDX Analyzer. Height, weight, waist-to-hip ratio, blood pressure, mood, sleep quality, and grit were also measured. Body composition was measured using DEXA. Data were analyzed using Prism GraphPad version 8.0. Significance was set at P < 0.05. Results: There were no significant changes in body weight, BMI, waist-to-hip ratio, or body composition within or between each group. However, an increase in bone mineral density was observed within all groups( P < 0.05). There was no effect of diet on plasma glucose and lipid levels. In addition, there was no change in blood pressure within each group. However, diastolic blood pressure decreased ( P < 0.05) in all groups. There were no changes in mood and grit. However, sleep quality improved within all groups ( P < 0.05). In addition, grip strength improved ( P < 0.05) within all groups. Conclusions: The preliminary results of this study indicate that incorporating white potatoes, processed potatoes, or starch carbohydrates into a higher protein diet, does not influence markers of cardiometabolic health in adults with metabolic syndrome. Higher protein diets, may improve secondary outcomes such as sleep quality, bone mineral density, and grip strength. However, a larger study population is needed. Funding Sources: Alliance for Potato Research and Education.